PERSEPSI NASABAH TERHADAP KUALITAS LAYANAN DAN KEAMANAN DIGITAL (CYBERCRIME) DALAM MEMBANGUN LOYALITAS PENGGUNA M-BANKING DI BSI KOTA JAMBI - Tiara Dwinda Hafhiz; Ahmad Syahrizal; Syahril Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Digital transformation in the Islamic banking industry has driven Bank Syariah Indonesia (BSI) to migrate its mobile banking service from BSI Mobile to the new BYOND by BSI platform. While the migration is intended to improve service quality and transaction security, the process has still been accompanied by technical issues (login failures, delayed OTP delivery, system errors) and customer concerns about cybercrime threats such as phishing, data theft, and ransomware, as illustrated by the 2023 LockBit 3.0 ransomware incident. This study aims to analyze customer perceptions of digital service quality and cyber security in BSI's mobile banking services, and to identify BSI's efforts to maintain trust and build user loyalty. The research applies a descriptive qualitative approach conducted at BSI's Jambi Pattimura Branch Office. Primary data were collected through in-depth interviews with purposively selected customers and bank staff, supported by non-participatory observation and documentation study. Data validity was ensured through source, technique, and time triangulation as well as member checking, while data analysis followed the interactive model of Miles and Huberman (data reduction, data display, and conclusion drawing). The theoretical framework draws on perception theory, the SERVQUAL model of service quality, the concept of cybercrime in digital banking, customer loyalty theory, and the principles of Islamic mobile banking. Preliminary findings indicate that customer perceptions of BSI's service quality and digital security are generally positive, although digital security literacy among customers remains uneven, indicating a continued need for education. This study contributes theoretically by integrating service quality and cyber security within the context of Islamic banking customer loyalty, and practically by informing BSI's efforts to strengthen its digital security systems and service quality.